Multimodal Approach to Language Learning: Integration of Technology to Improve Understanding and Effective Communication in the Digital Era - Mustakim Sagita; Novita Diana (Universitas Islam Negeri Palopo, 2026)
This study aims to analyze the effectiveness of a multimodal approach in improving students' language learning comprehension and communication skills. The multimodal approach integrates various modalities, such as text, images, sound, video, and digital technology, compared to the monomodal method which only uses one modality. This study used a quasi-experimental design with two groups, namely the control group and the experimental group, with a total of 60 students. The instruments used included pre-test and post-test, student perception questionnaires, classroom observations, and semi-structured interviews. The results showed that the experimental group taught with a multimodal approach experienced a significant increase in language comprehension, averaging 25%, while the control group increased by only 10%. In addition, students who used the multimodal approach reported higher levels of motivation and engagement in the learning process. Observations showed that technology plays an important role in creating an interactive and dynamic learning environment. However, there are challenges related to equitable access to technology among students. In conclusion, the multimodal approach proved more effective at improving students' language comprehension and communication skills than the monomodal method. This study recommends developing technological infrastructure, providing teacher training, and integrating multimodality into the curriculum to maximize the benefits of this method.